Coping strategies used by traumatic spinal cord injury patients in Sri Lanka: a focus group study. Issue 20 (24th September 2016) - Arya, Sumedha; Xue, Siqi; Embuldeniya, Amanda; Narammalage, Harsha; da Silva, Tricia; Williams, Shehan; Ravindran, Arun
Abstract: Purpose: Psychosocial consequences of traumatic spinal cord injury (SCI) have been well documented in Western populations, but there is no published literature on such incidence in the Sri Lankan population. The purpose of this study was to explore the psychosocial impact of SCI in a Sri Lankan population and to examine this population's coping mechanisms. Methods: Participants were recruited purposively at the Ragama Rheumatology and Rehabilitation Hospital, the sole rehabilitation facility for SCI patients in Sri Lanka. Focus groups were conducted with 23 consenting individuals. Interview transcripts were analysed using descriptive thematic analysis. Results: Four domains of life impact, three types of active coping strategies and four types of external supports were identified. Decreased ambulation and burden on family life were significant concerns for male and female participants alike. Religious practices were reported most frequently as active coping strategies, followed by positive reframing and goal-setting. Reported external supports included guided physiotherapy, informational workshops, social support and peer networks. Conclusion: Rehabilitation efforts for Sri Lankan SCI patients should be sensitive to psychosocial concerns in addition to physical concerns in order to help patients re-integrate into their family lives and community. Furthermore, religious practices should be respected as possible aids to rehabilitation. Implications for Rehabilitation: Rehabilitative efforts should be conscientious of patients' psychosocial well-being in addition to their physical well-being. Hospital-based rehabilitative efforts for traumatic spinal cord injury patients should promote functional independence and community re-integration. Spiritual and/or religious practices should be respected as ways by which traumatic spinal cord injury patients may confront personal challenges that arise following injury.